2019
DOI: 10.1136/bmjpo-2019-000486
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental delay in normocephalic children with in utero exposure to Zika virus

Abstract: Neurodevelopment in 29 normocephalic children with in utero exposure to Zika virus (ZIKV) was evaluated by the Bayley Scales of Infant and Toddler Development-Third Edition. Ten (35%) infants presented neurodevelopment delay. Language, cognitive and motor delays were identified in 9 (31%), 4 (14%) and 1 (3%) infants, respectively. Children exposed to ZIKV in utero must undergo careful evaluations for the early detection of any neurodevelopment delays in order to implement prompt intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 8 publications
3
81
0
1
Order By: Relevance
“…Faiçal et al 29 evaluated 29 normocephalic children with in utero exposure to Zika virus by the Bayley III. Ten (35%) infants presented neurodevelopment delay.…”
Section: Discussionmentioning
confidence: 99%
“…Faiçal et al 29 evaluated 29 normocephalic children with in utero exposure to Zika virus by the Bayley III. Ten (35%) infants presented neurodevelopment delay.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates born with congenital Zika syndrome (CZS) present severe microcephaly, eye loss, brain damage (including ventriculomegaly, intracranial calcifications, and skull collapse), congenital contractures, and hypertonia [ 6 , 7 ]. Healthy at birth not-infected children with in-uterus exposure to ZIKV may also develop psychomotor delays, poor reactions to external stimulation, generalized spastic dystonia, and other neurodevelopmental delays during childhood [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the studies of the children born without microcephaly, it would be important to describe neuroimaging and postnatal head circumference measurements, which was not the case for all of them. 6,9,19,20 Previous evidence has shown that some of those children will develop microcephaly only postnatally, 3 and others may have typical neuroimaging findings, but without microcephaly. Thus, it is possible that those studies may be describing two different populations, both without microcephaly at birth, but possibly with different prognosis: one of infants with structural neurological abnormalities and the other of children without neuroanatomical damage.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies describing the children born without microcephaly found suboptimal developmental scores, especially in the language domain, 9,10 but no comparison groups were described. Indeed, some of those children may have had a milder form of ZIKV-induced neurological impairment, but the socioeconomic context could be a cofounder for a lower language and cognitive development.…”
Section: Discussionmentioning
confidence: 99%